449 Neoadjuvant cyclic dinucleotides combined with interleukin-2 and anti-PD-1 antibody limit lung metastasis of orthotopic breast tumors through prolonged NK cell activation. (10th December 2020) - Milling, Lauren; Irvine, Darrell
Abstract : Background: Cyclic dinucleotides (CDN) – agonists of stimulator of interferon genes – can initiate potent anti-tumor immunity by activating antigen presenting cells which prime CD8+ T cells. 1 Recent studies have also highlighted CDN activation of NK cells via IL-15 in T cell-resistant tumors. 2 Thus far, limited analysis has been made of the impact of CDN-based therapies on cancer metastasis. We employed a surgical resection model of metastatic mammary carcinoma to examine the effects of surgery – a predominant breast cancer intervention – and lung metastasis on neoadjuvant therapy with CDNs combined with other clinically-relevant immunotherapies including IL-2 and anti-PD-1. 3 Methods: 4T1-luciferase cells were inoculated in the mammary fat pad, palpable tumors were treated with immunotherapy starting eight days later, any remaining primary tumor was surgically resected on day 17, and metastases were monitored by luciferase imaging. Combinations of intratumoral bisphosphorothioate 2'3' c-di-AMP (CDN), intraperitoneal (i.p.) albumin-IL2 fusion protein (Alb-IL2), and i.p. anti-PD-1 were tested in this model by measuring primary tumor growth and monitoring overall survival. CD8+ T cells, CD4+ T cells, or NK cells were depleted using anti-CD8 (2.43), anti-CD4 (GK1.5), and anti-asialo-GM1 antibodies, respectively, administered i.p. every 3 days beginning one day prior to treatment initiation. Immunophenotyping of primary tumors and lungs was conducted at several timepoints after starting therapy. Results: In mice bearing orthotopic 4T1-luciferase tumors, administration of three doses of CDN resulted in no cures in the absence of surgical resection. When administered prior to surgical resection CDN monotherapy yields a 20% cure rate and enhanced median overall survival compared to untreated mice (median survival 44.5 days vs 38 days, p=0.0026). Combination of CDN with Alb-IL2 and anti-PD-1 substantially improved survival, with 60% of mice surviving long-term. Through cellular depletions we determined that neither CD8+ nor CD4+ T cells were required for efficacy in this neoadjuvant therapy model, while NK cell depletion decreased survival rate by approximately 50%. Lung immunophenotying of CDN/Alb-IL-2/anti-PD-1-treated mice revealed a near doubling of the absolute NK cell count compared to untreated controls. More strikingly, lung infiltrating NK cells in the CDN/Alb-IL2/anti-PD-1 cohort exhibited prolonged granzyme B production compared to CDN monotherapy (6.24x higher after 6 days) and Alb-IL2 monotherapy (25x higher after 6 days) cohorts. Conclusions: Our findings suggest that combining intratumoral CDN with systemic Alb-IL2 and anti-PD-1 can delay the growth of primary breast tumors and limit metastatic outgrowth in the lungs. Efficacy is attributed to sustained cytotoxicity of NK cells. Ethics Approval: All mouse experiments were approved by MIT's Committee on Animal Care, protocol #0720-070-23. References: Corrales L, et al. Direct activation of STING in the tumor microenvironment leads to potent and systemic tumor regression and immunity. Cell Reports 2015; 11 :1018–30. Nicolai CJ, et al. NK cells mediate clearance of CD8+ T cell-resistant tumors in response to STING agonists. Science Immunology 2020; 5:eaaz2738. Al-Sahaf O, et al. Surgical injury enhances the expression of genes that mediate breast cancer metastasis to the lung. Ann Surg 2010; 252 :1037–43.